How to win friends and influence people : updated for the next generation of leaders - Carnegie, Dale (New York : Simon & Schuster, 2022)
An updated edition of Dale Carnegie$1 (Bs timeless guide to interpersonal success, revised with examples and principles for leadership in the 21st century.s
First published in 1936; this edition includes updated examples and modern leadership insights.
Keywords: Interpersonal relations; Success; Self-actualization (Psychology).; Leadership